Goserelin toxicities and preferences for ovarian suppression method in pre‐menopausal women with breast cancer. Issue 10 (October 2016) - Hsieh, A. H.‐C.; Kichenadasse, G.; Vatandoust, S.; Roy, A.; Sukumaran, S.; Karapetis, C. S.; Martin, H.; Chong, L. C.; Koczwara, B.
Abstract : Background: Goserelin, a form of medical ovarian suppression, is an effective treatment for pre‐menopausal women with breast cancer (PMBC). Meta‐analysis data showed that similar efficacy is achieved with medical ovarian suppression and non‐pharmacological ovarian suppression (NPOS) – oophorectomy or ovarian irradiation. The acceptance rate of NPOS remains low. Aims: This study explored the reported toxicities of PMBC women and their preferred ovarian suppression method whilst on goserelin. Methods: A postal survey consisting of 22 study‐specific questions was sent to PMBC women who received goserelin at the Flinders Medical Centre. Results: Nineteen women were identified from the database; 12 versus 7 women received goserelin in the adjuvant versus metastatic setting respectively. Thirteen (68.4%) responded to the survey. Women in the adjuvant cohort were more likely to report toxicities. The most common were hot flushes (100% vs 50% P = 0.033), myalgia/arthralgia (71.4% vs 16.7%, P = 0.048) and decreased libido (57/1% vs 16.7%, P = 0.135). NPOS was recalled to be offered to five (38.5%) women, with acceptance by one BRCA2 carrier. NPOS was declined initially due to fear of procedure, surgical/anaesthetic risk, invasiveness and planned future pregnancies. If given the option, upfront oophorectomy was indicated in seven (53.8%) women due to inconveniences with monthly goserelin. Conclusion: Half of PMBC women indicated a preference to NPOS, but only a minority recollected NPOS being discussed. Inconvenience with monthly goserelin is the main driver toward a preference of favouring NPOS. Clarification from larger trials that research patients' decision process and preferences regarding ovarian suppression is needed to validate our findings.